Analisis Program Z-Talks sebagai Program Unggulan Jabar Bergerak Zillenial - Deden Gunawan; Maya Amalia Oesman Palapah (UNISBA Press, 2024)
Abstract. Non-governmental organizations are located in a competitive session due to the rapid growth and development, both in terms of number and diversity of roles. Jabar Bergerak Zillenial is one of the NGOs that accommodates young people in West Java to collaborate in various actions in the fields of humanity and education. MPR strategies can contribute to organizational goals and image building. Based on this, the researcher intends to find out the implementation of marketing public relations strategies carried out by Jabar Bergerak Zillenial through the Z-talks program. This research uses a qualitative method with a case study approach, and data collection techniques are carried out by observation, interviews and documentation. The results of this study are MPR Strategy Planning carried out is to identify problems and opportunities, determine targets, limits and forms of strategy. The implementation process includes communication management, determining publication strategies, and ends with evaluation every three months. Abstrak. Non-govermental Organization terletak pada sesi kompetitif yang disebabkan adanya pertumbuhan dan perkembangan yang kian semakin pesat, baik dari sisi jumlah maupun keberagaman peran. Jabar Bergerak Zillenial merupakan salah satu NGO yang mewadahi anak muda Jawa Barat untuk berkolaborasi dalam berbagai aksi di bidang kemanusiaan dan Pendidikan. Strategi MPR dapat berkontribusi terhadap tujuan dan pembentukan citra organisasi. Berdasarkan hal tersebut peneliti bermaksud untuk mengetahui implementasi strategi marketing public relations yang dilakukan Jabar Bergerak Zillenial melalui program Z-talks. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus, serta teknik pengumpulan data yang dilakukan dengan observasi, wawancara dan dokumentasi. Hasil penelitian ini adalah Perencanaan Strategi MPR yang dilakukan adalah mengidentifikasi masalah dan peluang, menentukan target, batasan serta bentuk strategi. Proses Pelaksanaan meliputi pengelolaan komunikasi, menentukan strategi publikasi, serta diakhiri dengan Pengevaluasian setiap tiga bulan sekali.